Coupling of Polo kinase activation to nuclear localization by a bifunctional NLS is required during mitotic entry - David Kachaner (Nature Portfolio, 2017)
Drosophila Polo kinase is the founding member of the Polo-Like Kinase (PLK) family and a master regulator of mitosis and cytokinesis. Here the authors uncover a molecular mechanism for the spatiotemporal regulation of Polo kinase during mitotic entry through a phosphorylation event that triggers nuclear import.